The Soul of Modernity: Unkown Articles by José María Llanas Aguilaniedo (Castilla. Estudios de Literatura, 2013)
The aim of this paper is to analyse a group of articles published in press by the fin-de-siècle writer José María Llanas Aguilaniedo (1875-1921) which have not been documented before. As well as we increase the corpus documented on Llanas Aguilaniedo, this paper annalyse theses texts within the frame of other novels and essays by Llanas Aguilaniedo and the fin-de-siècle culture.